Positivity Expansion to Signed Solution for Doubly Nonlinear Parabolic Equations (Jagannath University Journal of Science, 2024)
We investigate doubly nonlinear parabolic equation with sign changing solutions. We established the expansion of positivity to the sign changing solution within a parabolic domain which is the key elements to achieve the regularity results.Jagannath University Journal of Science, Volume 10, Number I, Jun. 2023, pp. 64−74